PepT1-targeted nanodrug based on co-assembly of anti-inflammatory peptide and immunosuppressant for combined treatment of acute and chronic DSS-induced ColitiS - Zhang, Daifang; Jiang, Longqi; Yu, Fengxu; Yan, Pijun; Liu, Yong; Wu, Ya; Yang, Xi (Frontiers in Pharmacology, 2024)
Introduction Inflammatory bowel disease (IBD), as a chronic and recurrent inflammatory bowel diseases with limited therapeutic outcomes, is characterized by immune disorders and intestinal barrier dysfunction. Currently, the most medications used to cure IBD in clinic just temporarily induce and maintain remission with poor response rates and limited outcomes. Therefore, it is urgently necessary to develop an appropriate therapeutic candidate with preferable efficacy and less adverse reaction for curing IBD. Methods Five groups of mice were utilized: control that received saline, DSS group (mice received 2.5% DSS or 4% DSS), KPV group (mice received KPV), FK506 group (mice received FK506) and NPs groups (mice received NPs). The effect of NP on the inflammatory factors of macrophage was evaluated using CCK-8, quantitative polymerase chain reaction (PCR), Elisa and Western blot (WB). Immunofluorescent staining revealed the targeting relationship between NP and Petp-1. Immunohistochemistry staining showed the effect of NP on tight junction proteins. Moreover, in vivo animal experiments confirmed that NPs reduced inflammatory levels in IBD. Results and Discussion After administering with NPs, mice with DSS-induced acute or chronic colitis exhibited significant improvement in body weight, colon length, and disease activity index, decreased the level of the factors associated with oxidative stress (MPO, NO and ROS) and the inflammatory cytokines (TNF-α, IL-1β and IL-6), which implied that NPs could ameliorate murine colitis effectively. Furthermore, treating by NPs revealed a notable reduction of the expressions of CD68 and CD3, restoring the expression levels of tight junction proteins (Claudin-5, Occludin-1, and ZO-1) were significantly restored, surpassing those observed in the KPV and FK506 groups. which indicated that NPs can reduce inflammation and enhance epithelial barrier integrity by decreasing the infiltration of macrophages and T-lymphocytes. Collectively, those results demonstrated the effectively therapeutic outcome after using NPs in both acute and chronic colitis, suggesting that the newly co-assembled of NPs can be as a potential therapeutic candidate for colitis.